PENGEMBANGAN MEDIA MOVIE MAKER PADA MATA PELAJARAN KEARSIPAN KELAS X ADMINISTRASI PERKANTORAN - Fika Dwi Rahmania; Sutrisno -; I Nyoman Suputra (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
Abstract: The purpose of this research is the instructional medium movie maker in the basic competence that is Identifying the Archival Equipment and Materials also Explaining the Entry and Exit Mail for students in grade X of Office Administration program membership SMK PGRI 6 Malang. This study used a model of development ASSURE combined, and it is modified with 4D developmental model thus obtained 7 stages of development. Based on the validation results of the experts of media and material, the experts of media showed the percentage of 100% and the experts of material showed the percentage of 96.87%that those numbers showed that the instructional medium movie maker has very valid criteria. The results of the validation by a small group of students showed a percentage of 82% was obtained from the results of the empirical score divided by the maximum score. The results of the validation by a large group of students showed a percentage of 81.7% was obtained from the results of the empirical score divided by the maximum score.